Titanium lithium ion sieve based on illumination assistance, synthetic method and application

Through the titanium lithium ion sieve synthesis method based on light-assisted titanium lithium ion sieve synthesis method, the adsorption and desorption kinetics of lithium ion sieve materials are enhanced, and the problem of slow kinetics of existing materials is solved, and efficient lithium ion extraction performance is achieved.

CN119612583AActive Publication Date: 2025-03-14SICHUAN UNIV

Patent Information

Application Number
CN202411794863.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The kinetics of existing lithium ion sieve materials are slow during adsorption and desorption, and it is difficult to accelerate both processes at the same time, affecting the efficiency of lithium ion extraction.

Method used

The titanium lithium ion sieve synthesis method based on light assisted is adopted to construct phase boundaries through solid phase sintering and acid treatment, and electron transfer at the two phase interface is enhanced by selective doping of metal ions, and the space charge region is regulated in combination with light to optimize adsorption and desorption kinetics.

Benefits of technology

The rapid transmission of lithium ions and efficient lithium-enhancing performance have been achieved, the adsorption capacity reaches 22.95mg·g-1, the absorption rate can reach up to 13.10mg·g-1·h-1, and the desorption efficiency is as high as 99.5%, which significantly improves the commercial application potential of lithium ion sieve materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612583A_ABST
    Figure CN119612583A_ABST
Patent Text Reader

Abstract

The invention belongs to material science and chemical engineering, and particularly relates to a titanium lithium ion sieve based on illumination assistance, a synthesis method and application. A synthesis method of a titanium lithium ion sieve based on illumination assistance comprises the following steps: S1, mixing and dissolving a titanium source and a lithium source in a solvent, grinding to obtain a mixture, drying the mixture, and heating in an air atmosphere to obtain a metatitanic acid and orthotitanic acid composite material precursor; and S2, adding a solvent and a metal source into the metatitanic acid and orthotitanic acid composite material precursor in the S1, grinding, drying to obtain mixed powder, heating the powder to obtain a metal source doped orthotitanic acid and metatitanic acid composite material, and soaking the metal source doped orthotitanic acid and metatitanic acid composite material in an acid solution to obtain the titanium lithium ion sieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to material science and chemical engineering, and specifically relates to a titanium-based lithium ion sieve based on light assistance, a synthesis method and an application. Background Art

[0002] With the rapid development of energy storage technology, electric vehicles and 3C (computer, communication and consumer electronics) products, the demand and output of lithium-ion batteries have increased rapidly, and the consumption of lithium resources has increased dramatically. Since about 70% of the world's lithium resources exist in liquid phase, including salt lakes, brine and seawater, it is urgent to develop low-cost and efficient liquid phase lithium resource extraction technology.

[0003] At present, the main technology for extracting lithium from brine is the lime-soda evaporation method based on evaporation technology. However, this method requires a long cycle (usually one to two years) to produce lithium from brine. In addition, the large amount of water consumption and waste generation reduces its energy efficiency, which has a greater impact on the fragile ecological environment in the high-altitude areas where salt lakes are located. In comparison, the liquid phase adsorption method based on lithium ion sieve materials is a promising lithium extraction method due to the advantages of LIS adsorption method such as low energy consumption, high lithium absorption capacity, environmental friendliness and excellent lithium selectivity. It is considered to be one of the most promising liquid phase lithium extraction technologies for commercialization.

[0004] Commonly used lithium ion sieve materials mainly include: manganese-based lithium ion sieve (LMO) and titanium-based lithium ion sieve (LTO). The severe dissolution loss of Mn in the manganese-based lithium ion sieve during the acid elution process has an adverse effect on the cycle stability. On the contrary, titanium-based lithium ion sieve has better chemical stability due to the presence of Ti-O bonds and has been widely used in liquid phase lithium extraction. Titanium-based materials mainly include orthotitanic acid and metatitanic acid. Orthotitanic acid has excellent adsorption kinetics, but low adsorption capacity, while metatitanic acid has excellent adsorption capacity, but poor adsorption kinetics, and neither can meet commercial applications. In order to combine the advantages of the two, some researchers have proposed to compound the two and use the interphase regulation effect on the solid-phase transport of lithium ions to achieve rapid adsorption and desorption of lithium ions. However, the force of the interphase electric field between the two phases is limited and is a single-phase force. How to enhance the field strength between the two phases and achieve faster kinetic processes in both adsorption and desorption processes through external field assistance remains to be studied. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis, comprising the following steps:

[0006] S1: mixing a titanium source and a lithium source and dissolving them in a solvent, grinding to obtain a mixture, drying the mixture, and heating the mixture in an air atmosphere to obtain a metatitanate-orthotitanate composite material precursor;

[0007] S2: Add a solvent and a metal source to the metatitanate orthotitanate composite material precursor of S1, grind and dry to obtain a mixed powder, heat the powder to obtain a metal source-doped orthotitanate orthotitanate composite material, and soak the metal source-doped orthotitanate orthotitanate composite material in an acid solution to obtain a zinc-doped metatitanate orthotitanate inhibition structure lithium ion sieve, i.e., a titanium-based lithium ion sieve.

[0008] Furthermore, the mass ratio of the titanium source to the lithium source described in S1 is 3:1-1:2.

[0009] Furthermore, the temperature in the heating process described in S2 is 500-1000° C. and the time is 1 to 4 hours.

[0010] Furthermore, the mass ratio of the metal source in S2 to the orthotitanate-metatitanate composite material in S1 is 1:20-1:80.

[0011] Furthermore, the temperature of the heating process described in S1 is 700° C. to 800° C., and the heating time is 4 hours.

[0012] Furthermore, the lithium source described in S1 is any one of lithium carbonate, lithium acetate, and lithium oxide.

[0013] Furthermore, the metal source described in S2 is any one of salts and oxides, sulfides, selenides and halides containing transition metals.

[0014] Furthermore, the titanium source described in S1 is any one of titanium dioxide, amorphous titanium dioxide, and hydrated titanium dioxide intermediates.

[0015] A titanium-based lithium ion sieve based on light assistance has a heterogeneous structure of uniformly compounded metatitanic acid and orthotitanic acid.

[0016] The invention discloses an application of a titanium-based lithium ion sieve based on light assistance, wherein the titanium-based lithium ion sieve is used in the preparation of a high-efficiency lithium ion sieve.

[0017] Beneficial Effects

[0018] (1) The present invention provides a method for synthesizing titanium-based lithium ion sieves based on light-assisted sintering. This method constructs abundant phase boundaries inside the lithium ion sieve material through simple solid-phase sintering and acid treatment, and further intensifies the electron transfer at the interface between the two phases through selective doping of metal ions. Due to the additional driving force of the enhanced space charge region at the phase boundary, Li + It can be quickly transferred between the two phases. However, this force is only unidirectional and cannot accelerate the adsorption and desorption processes at the same time. Therefore, based on the generally good light conditions in the salt lake area, a method based on light regulation of the space charge region to enhance the dual process kinetics of lithium ion adsorption and desorption is proposed.

[0019] (2) Through the light-assisted titanium-based lithium ion sieve provided by the present invention, the optimized two-phase composite lithium ion sieve material can reach 22.95 mg·g under the action of the space charge region even under neutral conditions. -1 The capacity can reach up to 13.10 mg g during lithium extraction. -1 ·h -1 Li + The absorption rate can be effectively regulated by light to further optimize the lithium extraction performance of the material, which can reach up to 25.13 mg g under neutral conditions. -1 The lithium extraction capacity can reach 14.92 mg g -1 ·h -1 Li + The absorption rate is high, and the acid-washing desorption efficiency is as high as 99.5%; it shows excellent lithium ion adsorption and desorption performance. This work is of great significance for accelerating the practical commercial application of titanium-based lithium ion sieve materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.

[0021] In the figure:

[0022] Figure 1 XRD diagrams of Examples 1 to 3 of the present invention;

[0023] Figure 2 are morphological diagrams of Examples 1 to 3 of the present invention;

[0024] Figure 3 The lithium extraction performance diagram of Examples 1 to 3 of the present invention;

[0025] Figure 4 This is the dissolution diagram of titanium in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0026] The following is a description of the embodiments of the present invention and the attached Figures 1 to 4 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] This article provides a method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis, comprising the following steps:

[0028] S1: First, a titanium source and a lithium source are mixed by a solid phase method to prepare a heterostructure composite material precursor composed of metatitanic acid and orthotitanic acid, and a heterostructure composite material composed of metatitanic acid and orthotitanic acid is obtained after acid washing;

[0029] S2: doping the doping metal source and the composite material precursor in proportion under high temperature and gas atmosphere to obtain a heterogeneous structure composite material precursor in which the metal is selectively doped into the titanate phase, and after acid washing, a metal-doped titanate orthotitanate inhibition structure lithium ion sieve is obtained.

[0030] Example 1

[0031] S1: 1.65 g of lithium acetate and 1.25 g of titanium dioxide were mixed in ethanol, and then the mixture was ground for 30 minutes to ensure sufficient mixing; the mixture was placed in a blast drying oven and dried until the ethanol was completely volatilized; and then the mixture was heated at a temperature of 700° C. in an air atmosphere for 4 hours to obtain a metatitanic acid orthotitanic acid composite material precursor;

[0032] S2: Take 0.4g of heterostructure composite material precursor LTO, add 15ml of ethanol, add magnesium chloride, the mass ratio of magnesium chloride to heterostructure composite material precursor is 1:80; then grind for 30min to ensure sufficient mixing; obtain mixed powder; place the mixed powder in a forced air drying oven, and dry it at 70°C for 50 minutes until the ethanol is completely volatilized; heat the mixed powder at 800°C in an air atmosphere for 4 hours; then soak the powder in a 0.25M HCl solution (solid-liquid ratio of 10g / L) for 24 hours to obtain a metal-doped metatitanate / orthotitanate heterostructure titanium-based lithium ion sieve.

[0033] Example 2

[0034] S1: lithium acetate and titanium dioxide are mixed in ethanol, and then the mixture is ground for 30 minutes to ensure sufficient mixing; the mixture is placed in a blast drying oven and dried until the ethanol is completely volatilized; and then the mixture is heated at a temperature of 700° C. in an air atmosphere for 4 hours to obtain a metatitanic acid and orthotitanic acid composite material precursor;

[0035] S2: Take 0.4g of heterostructure composite material precursor LTO, add a certain amount of ethanol, add magnesium chloride, the mass ratio of magnesium chloride to heterostructure composite material precursor is 1:40; then grind for 30 minutes to ensure sufficient mixing; obtain mixed powder; place the mixed powder in a forced air drying oven, and dry it at 70°C for 50 minutes until the ethanol is completely volatilized; heat the mixed powder at 800°C in an air atmosphere for 4 hours; then soak the powder in a 0.25M HCl solution (solid-liquid ratio of 10g / L) for 24 hours to obtain a metal-doped metatitanate / orthotitanate heterostructure titanium-based lithium ion sieve.

[0036] Example 3

[0037] S1: lithium acetate and titanium dioxide are mixed in ethanol, and then the mixture is ground for 30 minutes to ensure sufficient mixing; the mixture is placed in a blast drying oven and dried until the ethanol is completely volatilized; and then the mixture is heated at a temperature of 700° C. in an air atmosphere for 4 hours to obtain a metatitanic acid and orthotitanic acid composite material precursor;

[0038] S2: Take 0.4g of heterostructure composite material precursor LTO, add a certain amount of ethanol, add magnesium chloride, the mass ratio of magnesium chloride to heterostructure composite material precursor is 1:20; then grind for 30 minutes to ensure sufficient mixing; obtain mixed powder; place the mixed powder in a blast drying oven, and dry it at 70°C for 50 minutes until the ethanol is completely volatilized; heat the mixed powder at 800°C in an air atmosphere for 4 hours; then soak the powder in a 0.25M HCl solution (solid-liquid ratio of 10g / L) for 24 hours to obtain a metal-doped metatitanate / orthotitanate heterostructure titanium-based lithium ion sieve.

[0039] The present invention provides a method for synthesizing a titanium-based lithium ion sieve based on light-assisted. During the whole process, when the material is applied to the lithium extraction scene, adsorption is carried out in a dark field, and desorption is carried out under natural light, which means "based on light-assisted". The two-phase composite material obtained by this method has a unique heterogeneous structure, and there is a space charge region, which affects the solid-phase transmission rate of lithium ions. The space charge region can be enhanced by doping with metal ions, and combined with the regulation of light, the extraction and removal of lithium ions are promoted respectively. The material preparation process of the present invention is simple, energy-saving and environmentally friendly, and low in cost. At the same time, it makes full use of the rich light resources in the western region where salt lakes are distributed in large quantities, respectively enhances the adsorption and desorption rates, and improves the lithium extraction efficiency; and the method uses light to regulate the space charge region of the ion sieve during the adsorption and desorption process, so that its effect is enhanced during the adsorption process, and its effect is weakened during the desorption process, and the lithium extraction performance of the material is optimized by the regulation mechanism of light on the space charge region.

Claims

1. A method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis, characterized in that: The following steps are involved: S1: mixing a titanium source and a lithium source and dissolving them in a solvent, grinding to obtain a mixture, drying the mixture, and heating the mixture in an air atmosphere to obtain a metatitanate-orthotitanate composite material precursor; S2: Add a solvent and a metal source to the metatitanate orthotitanate composite material precursor of S1, grind and dry to obtain a mixed powder, heat the powder to obtain a metal source-doped orthotitanate orthotitanate composite material, and soak the metal source-doped orthotitanate orthotitanate composite material in an acid solution to obtain a zinc-doped metatitanate orthotitanate inhibition structure lithium ion sieve, i.e., a titanium-based lithium ion sieve.

2. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The mass ratio of the titanium source to the lithium source described in S1 is 3:1-1:

2.

3. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The heating process described in S2 has a temperature of 500-1000° C. and a time of 1-4 hours.

4. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The mass ratio of the metal source in S2 to the orthotitanate-metatitanate composite material in S1 is 1:20-1:

80.

5. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The temperature of the heating process described in S1 is 700° C. to 800° C., and the heating time is 4 hours.

6. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The lithium source described in S1 is any one of lithium carbonate, lithium acetate, and lithium oxide.

7. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The metal source described in S2 is any one of salts and oxides, sulfides, selenides and halides containing transition metals.

8. The method for synthesizing a titanium-based lithium ion sieve based on light-assisted synthesis according to claim 1, characterized in that: The titanium source described in S1 is any one of titanium dioxide, amorphous titanium dioxide, and hydrated titanium dioxide intermediates.

9. A light-assisted titanium-based lithium ion sieve obtained by the synthesis method according to any one of claims 1 to 8, characterized in that: The titanium-based lithium ion sieve has a heterogeneous structure in which metatitanic acid and orthotitanic acid are uniformly compounded.

10. The use of a light-assisted titanium-based lithium ion sieve according to claim 9, characterized in that: The titanium-based lithium ion sieve is used in the preparation of a high-efficiency lithium ion sieve.

Citation Information

Patent Citations

  • Synthesis method of lithium extraction adsorbent

    CN110975795A

  • Titanium type lithium ion sieve and preparation method thereof

    CN113274971A

  • Preparation method of iron-doped titanium lithium ion sieve

    CN116637586A

  • Aluminum-doped titanium lithium ion sieve adsorbent as well as preparation method and application thereof

    CN117695995A

Cited By

  • Hydrogel-based water-energy-resource co-production solar evaporator and application thereof

    CN121377181A